Coexpression of hypoxia-inducible factors 1alpha and 2alpha, carbonic anhydrase IX, and vascular endothelial growth factor in nasopharyngeal carcinoma and relationship to survival. - Hui, E; Chan, A; Pezzella, F; Turley, H; To, K; Poon, T; Zee, B; Mo, F; Teo, P; Huang, D; Gatter, K; Johnson, P; et al. (2002)
PURPOSE: Tumor hypoxia is known to be associated with resistance to chemotherapy, radiotherapy, and poorer survival. Recently, it is shown that hypoxia induces the expression of hypoxia-inducible factor-1alpha and 2alpha (HIF-1alpha and HIF-2alpha), which then up-regulates the expression of downstream genes such as carbonic anhydrase IX (CA IX) and vascular endothelial growth factor (VEGF). EXPERIMENTAL DESIGN: We examined the expression of HIF-1alpha, HIF-2alpha, CA IX, and VEGF by immunohistochemistry in nasopharyngeal carcinoma (NPC) biopsies from 90 consecutive patients recruited between 1994 and 1997 in a randomized controlled trial of chemoradiation in locally advanced NPC and investigated their relationship with survival. RESULTS: HIF-1alpha was expressed in 52 of 90 (58%), HIF-2alpha in 6 of 89 (7%), CA IX in 51 of 90 (57%), and VEGF in 54 of 90 (60%) of tumors. Tumor HIF-1alpha expression correlated significantly with that of CA IX (P = 0.008) and VEGF (P = 0.003). High tumor HIF-1alpha expression was associated with a trend for poor overall survival (P = 0.06). Tumors with a positive hypoxic profile (defined as high expression of both HIF-1alpha and CA9) were associated with worse progression-free survival (P = 0.04). Tumors with both hypoxic and angiogenic profile (defined as high VEGF expression) were associated with a worse progression-free survival (P = 0.0095). CONCLUSION: Overexpression of HIF-1alpha, CA IX, and VEGF is common in NPC, which is probably related to hypoxia up-regulated expression involving a HIF-dependent pathway, and is associated with poor prognosis. Targeting the hypoxia pathway may be useful in the treatment of NPC.